2021
DOI: 10.1016/j.ultsonch.2021.105801
|View full text |Cite
|
Sign up to set email alerts
|

The combination of ultrasound and chlorogenic acid to inactivate Staphylococcus aureus under planktonic, biofilm, and food systems

Abstract: Highlights The synergistic bactericidal effect had produced by ultrasound (US) and chlorogenic acid (CA). US plus CA changed the morphology of S. aureus cells.. US plus CA led the leakage of internal constituents. US plus CA reduced the concentration of polysaccharide in biofilms. US plus CA reduced S. aureus in mutton by 1.14 log CFU/g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Further, when using US in combination with other disinfection strategies, low-frequency US is recommended and the cell membrane is considered as main attack target [ 50 ]. A recent study reported that US and chlorogenic acid can synergistically inactivate Staphylococcus aureus , mainly by disrupting cell membrane permeability [ 51 ]. Zhang et al [ 52 ] also reported the synergistic disinfection effects of US and citral against E. coli and Listeria monocytogenes via the acceleration of cell membrane damage.…”
Section: Resultsmentioning
confidence: 99%
“…Further, when using US in combination with other disinfection strategies, low-frequency US is recommended and the cell membrane is considered as main attack target [ 50 ]. A recent study reported that US and chlorogenic acid can synergistically inactivate Staphylococcus aureus , mainly by disrupting cell membrane permeability [ 51 ]. Zhang et al [ 52 ] also reported the synergistic disinfection effects of US and citral against E. coli and Listeria monocytogenes via the acceleration of cell membrane damage.…”
Section: Resultsmentioning
confidence: 99%
“…A nucleic acid release assay was performed to determine the number of ARGs released from damaged cells after each physical treatment [10] , [11] . In brief, ARE cells were treated with mild heat, sonication, and HS under the same conditions as those in the antimicrobial efficacy test.…”
Section: Methodsmentioning
confidence: 99%
“…At present, various physical treatments (e.g., ultraviolet radiation, heat, and cold plasma) have been proposed as solutions to control various foodborne pathogens, including ARB, in the food system [8] , [9] . For example, recent studies have reported that a combination of physical treatments may lead to the synergistic inactivation of various pathogenic bacteria, including Escherichia coli , Listeria spp., and Staphylococcus aureus [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . However, during bacterial inactivation, nucleic acids can be released from the dead bacteria into the food environment.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid is a major constituent of some traditional Chinese medicine preparations and it is endowed with many medicinal properties including antibacterial activity against many Gram-positive and Gram-negative organisms [ 129 , 130 ]. A significant synergetic bactericidal and antibiofilm effect was produced against S. aureus by the combination of ultrasound and chlorogenic acid treatment which was mediated through increasing the cell membrane permeability, release of ATP, and nucleic acids, and decreasing the exopolysaccharide contents in the biofilm [131] . Similarly, chlorogenic acid presented strong bactericidal and antibiofilm activity in the clinical isolates of Stenotrophomonas maltophilia including the trimethoprim/sulfamethoxazole resistant strain [132] .…”
Section: Antibacterials From Plant Originmentioning
confidence: 99%